PENERAPAN STRATEGI PEMBELAJARAN SCAFFOLDING PADA MATERI PENELITIAN SOSIAL SEBAGAI PEMECEHAN MASALAH SOSIAL - Yan Iqbal (Labor Program Studi Pendidikan Sosiologi, 2022)
This study aims to describe how scaffolding learning strategies are implemented in the classroom and what steps can be carried out by teachers and students in order to form their maximum abilities in studying sociology material, especially in social research material based on social problem solving. The approach used in this research method is qualitative with a phenomenological type and data collection is done naturally (natural setting). The results showed that there were stages of implementing the scaffolding strategy to help students understand social research material, including apperception stages, core activities and closing activities, while at the stage of improving students' abilities the teacher gave students the opportunity to choose their own research material, creating a class atmosphere that comfortable, setting shared goals, establishing a structure to achieve goals, considering student backgrounds, fostering independence and varying learning models.